Effects of Cyclic Nucleotides and Nucleoside Triphosphates on Stalk Formation in Caulobacter crescentus - Schmidt, Jean M. (1972)
Extensive stalk elongation in Skl mutants of Caulobacter crescentus occurs when they are grown in complete medium. This stalk elongation is less pronounced in synthetic medium with glucose as the sole carbon source than in complex peptone yeast extract medium. Addition of exogenous nucleoside triphosphates (adenosine triphosphate [ATP], guanosine triphosphate [GTP], cytidine triphosphate, and uridine triphosphate) inhibits stalk elongation of the Skl mutants, whereas cyclic guanosine 3′,5′-monophosphate (GMP) stimulates stalk elongation in the Skl strains grown in synthetic glucose medium. Cyclic GMP also produces stalk elongation in wild-type C. crescentus and concurrently produces a cell division defect resulting in cellular filament formation. Under conditions tested, cyclic adenosine 3′,5′-monophosphate and dibutyryl cyclic adenosine monophosphate did not enhance stalk elongation. Endogenous ATP and GTP levels in the mutants are significantly lower than corresponding nucleotide concentrations of the parent wild-type strains. Control of syntheses resulting in stalk formation in C. crescentus appears to be related to intracellular concentrations of nucleotides, with cyclic GMP as a prominent candidate for an important regulatory role in this aspect of morphogenesis.